EFFECTIVENESS OF AGRICULTURAL EXTENSION SERVICES IN REDUCING POVERTY AMONG FISH FARMERS IN THE COASTAL REGION OF ONDO STATE, NIGERIA - AKINBOYE OA (Innovare Journal of Agricultural Sciences, 2024)
Agricultural development is the foundation for economic growth and provides a primary means of food security, employment generation, and poverty reduction for Nigerians. These are also the very reasons motivating successive incumbent governments of Nigeria to initiate one type of agricultural intervention program or another to generate employment, attain food security, and aid in poverty reduction. The study assesses the effectiveness of agricultural extension services in reducing poverty among fish farmers in the coastal region of Ondo State, Nigeria. A well-structured interview schedule was used to collect data from the respondents and simple random sampling technique was used in selecting 80 respondents. Data collected was analyzed using frequency counts and percentage while Chi-square and Pearson product moment correlation was used for testing the hypotheses. Results of the socioeconomic characteristics show that more than half (58.7%) of the respondents were adults, male (68.7%), married (78.8%), literate (92.5%), having household size of <7 members (92.5%), earned an annual income of <#1,000,000 (73.7%), and having fish farming experience of <5 years (41.2%). Further analysis shows that catfish is mostly farmed by the respondents in the study area (72.5%), belong to one social group or the other (52.5%), and have access to agricultural extension agents (100%). Similarly, the study findings shows that all the respondents (100%) have access to all the different types of services rendered and the different types of agricultural extension services were rendered to the fish farmers which include technology transfer (93%), information and support services (90%), food safety and quality (89%), marketing and distribution (75%), sustainable fisheries (88%), credit and finance (96%), safety measures (100%), training to fish farmers (97%), input supply (88%), and technical expertise (92%). Furthermore, the types of agricultural extension services utilized by the fish farmers include information and support services (100%), food safety and quality (100%), credit and finance (100%), safety measures (100%), input supply (85%), and technical expertise (100%). Types of constraints militating effective utilization of agricultural extension service rendered identified by the fish farmers include weak linkages of research and training centers with extension workers and users (82%), lack of properly qualified/trained extension personal (100%), inadequate number of grass root workers (98%), lack of clear extension strategies (85%), emphasis on welfare than development (88%), much emphasis on technology than its transfer to end users (75%), inadequate infrastructure facilities (80%), and of the respondents and lack of incentives for field staff (100%). There was positive and significant relationships between respondents’ age (r=0.532; p≤0.05), number of years spent schooling (r=0.589; p≤0.05), household size (r=0.117; p≤0.05), annual income (r=0.515; p≤0.05), fish farming experience, (r=0.146; p≤0.05), and effectiveness of agricultural extension services in reducing poverty. The study recommended that more qualified/trained extension personnel should be employed and adequate incentives should be made available to the field staff.